Hubungan lingkungan belajar dengan prestasi belajar mahasiswa - Menik Sri Daryanti (Universitas Aisyiyah Yogyakarta, 2016)
This study aimed to analyze the relationship between the learning environment and utilization library by learning on student achievement. The study was observational analytic. The sampling technique used was purposive sampling, the samples are 40 fourth -semester students D-III Midwifery Sebelas Maret University of Surakarta. Measuring instruments used questionnaires and documentation GPA. Analysis of data using Pearson Product Moment. From the results of the correlation calculation, obtained rhitung = 0.428, with significant value 0,006 where rhitung = 0.428 rtabel = 0.312 and 0.006 significance value 0.05. This means that there is a relationship of learning environment and academic achievement of students, with the strength of the correlation was.